Fishing activities of frontier Etruscans: the hooks from Forcello di Bagnolo San Vito (MN) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2024)
The settlement of Forcello (Bagnolo S. Vito, Mantua) was located on the bank of a lake formed by the widening of the ancient Mincio. The river allowed goods to arrive via water transport and was also exploited for fishing activities, to supplement a mainly pork-based diet. This data is shown by recent zooarchaeological studies and by the 42 metal hooks found in sectors R-S 17-19, which haven't been fully published yet. In this dissertation, the two authors focus on creating a catalogue that looks at these artifacts from a typological point of view, giving details about their morphology and morphometry. The corpus is also discussed considering the contexts and the data on fish species collected, in order to provide a sufficiently comprehensive set of information.
Keywords: hook; fishing; Etruscans; settlement; Iron age; Etruria padana